(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the energy expenditure (EE) in a resistance training protocol with different volumes of a fixed weight by the alternating circuit method by segment in trained (TR) and untrained (UT) men. Method: The sample comprised, by volunteering, 18 men aged between 18 and 35 years. After being informed about the stages of the project, the volunteers carried out an assessment of their body composition, followed by the tests of a maximum repetition (1RM) and twenty maximum repetitions (20RM), and later retest. The protocol consisted of three circuit-training sessions with different training volumes (12, 16 and 20 repetitions) of a fixed weight of 20RM in the leg press, bench press, flexor table and front puller exercises, with 1-minute intervals between the exercises and 2 minutes between each lap, totaling 3 laps per session. For data analysis, the STATISTIC 7 software was used, adopting a significance of p<0.05. Results: It was found that the TR volunteers showed greater total work in relation to the UT volunteers in the sessions of 12 (TR=15820.80±2396.50; UT=10381.60±2660.374), 16 (TR=20919.95±3219.82; UT=12727.46±3143.99) and 20 repetitions (TR=21957.24±3470.21; UT=12959.57±4084.05). The same was observed in the EE of the exercise in the sessions of 12 (TR=85.01±14.72; UT=64.34±15.43), 16 (TR=111.10±25.97; UT=74.24±20.03) and 20 repetitions (TR=145.33±58.64; UT=78.69±24.21), and in the EE/repetitions in sessions of 12 (TR=0.59±0.10; DT=0.44±0.11), 16 (TR=0.59±0.13; UT=0.43±0.12) and 20 repetitions (TR=1.10±0.34; UT=0.43±0.13). Conclusion: The EE/repetitions were not affected in the sessions close to the concentric failure in this protocol for UT individuals, in contrast, for the TR group, the closer to the failure the greater the EE/repetitions.